181k views
3 votes
Use the distributive property to simplify the expression. -7(8-3)+x

User Zhao
by
6.0k points

1 Answer

4 votes

-35 + x is the simplified expression

Solution:

Given expression is:

-7(8 - 3) + x

We have to use the distributive property

By distributive property,

a(b + c) = ab + ac

Therefore,


-7(8 - 3) + x = (-7 * 8) + (-7 * -3) + x\\\\-7(8 - 3) + x = -56 + 21 + x\\\\Combine\ constants\\\\-7(8 - 3) + x = -35+x

Thus, distributive property is used to simplify the expression

User Dominik
by
5.8k points